Hebella macroplana Watson 2019 - Cantero, Álvaro Luis Peña (Zenodo, 2023)
Hebella macroplana Watson, 2019 (Figs. 2b–g, 3) Hebella macroplana Watson, 2019: 66–67, fig. 1f. Material examined. TAN0307/55 , a few hydrothecae and one gonotheca, on bryozoan (NIWA 114746). Description. Hydrotheca tubular, very large, straight, or slightly curved; wall smooth. Aperture circular, rim even, slightly everted; sometimes with a short renovation. Hydrotheca separated from a rather short pedicel by a thin diaphragm, rising to the centre. A ring of desmocytes present at diaphragm level. Diameter of hydrotheca distinctly increasing at diaphragm, then gently so up to about half-length of hydrotheca, and becoming constant thereafter, only slightly increasing at rim. Gonotheca markedly flat, thin in lateral view and very wide in frontal view. Aperture extending along its entire distal part. Measurements (in µm). Hydrotheca : height to diaphragm 1600–1800, diameter at aperture 500–570. Pedicel : length 150–200. Gonotheca : height 1250, diameter 250 (lateral view) and 920 (frontal view). Remarks. The gonothecae is very flat, resembling a mollusc shell or the gonotheca of some Halecium species. The present material completely agrees with Watson’s species in the shape and size of the hydrotheca. This represents the second record of the species and the first time the gonotheca has been described. Ecology and distribution. Hebella macroplana is a deep-water species. It was only known from its type locality, at eastern Bass Strait, Victoria (actually in the western Tasman Sea), where it was collected at depths between 4197 and 4133 m, growing on the stem of an antipatharian. Present material comes from off Antipodes Islands, at the eastern Bounty Plateau, and was collected at a depth of 2648−2650 m, epibiotic on a bryozoan. The material, with gonotheca, was collected in April. Published as part of Cantero, Álvaro Luis Peña, 2023, On some benthic hydroids from New Zealand deep waters, with the description of a new species, pp. 241-252 in Zootaxa 5389 (2) on pages 244-245, DOI:10.11646/zootaxa.5389.2.6, ...